Peningkatan Hasil Belajar Tematik Melalui Pendekatan Saintifik Pada Peserta Didik Kelas I A SD Inpres Ende 7 Kecamatan Ende Timur Kabupaten Ende Tahun Pelajaran 2018/2019 - Bergita Nirgaya (Program Studi Pendidikan Ekonomi, Universitas Flores, 2019)
The purpose of this study was to determine the application of thematic learning with scientific approaches and learning outcomes of class IA students of SD Inpres Ende 7. The type of research used was classroom action research with data collection techniques namely observation techniques, and tests. The results showed that the teacher's activity in the first cycle was not optimal in fostering new experiences that were meaningful and more dominant use of time to discuss themes mathematically, not optimal in making general phenomena available to later draw specific conclusions (inductive reasoning) or otherwise specific phenomena later draw conclusions as a whole (deductive reasoning). Learning outcomes are 36, 36%. In the second cycle there was an increase in teacher and student activities and 100% completeness, with an average of 78.18. It is concluded that thematic learning provides a charge for students to have comprehensive thinking skills (multi aspects), having a rational and empirical relationship. Scientific approach (scientific approach) provides space for students to observe, ask, try, process, present, conclude, and create. Thus students will use the skills to investigate and or inquiry against a phenomenon or symptoms. It is recommended to teachers to optimize the stages of thematic learning with a scientific approach to familiarize students wit